China's urban Christians : a light that cannot be hidden - Fulton, Brent (Cambridge, United Kingdom : The Lutterworth Press, 2016)
"Looks at how massive urbanization is redrawing not only the geographic and social landscape of China, but in the process is transforming China's growing church as well. The purpose of this book is to explore how Christians in China perceive the challenges posed by their new urban context and to examine their proposed means of responding to these challenges. Although not primarily political in nature, these challenges nonetheless illustrate the complex interplay between China's Christian community and the Chinese party-state as it comes to terms with the continued growth and increasing prominence of Christianity in modern China."--
Introduction -- The context for change -- New wineskins -- A shifting battleground -- Into the light -- The church's global mandate -- The quest for unity -- Testing the limits -- Conclusion.
Includes bibliographical references (pages 137-142).
PDF (JSTOR, viewed Apr. 24, 2017).
Keywords: China -- Church history; Christianity -- China; Church and social problems -- China; Christian sociology -- China; Christianity and politics -- China; Urbanization -- China; Christian sociology; Christianity; Christianity and politics; Church and social problems; Urbanization; China; RELIGION / Christianity / History; Church history; Electronic books